Population-Based Screening of Newborns: Findings From the NBS Expansion Study (Part One) - Brower, Amy; Chan, Kee; Williams, Marc; Berry, Susan; Currier, Robert; Rinaldo, Piero; Caggana, Michele; Gaviglio, Amy; Wilcox, William; Steiner, Robert; Holm, Ingrid A.; Taylor, Jennifer; et al. (Frontiers in Genetics, 2022)
Each year, through population-based newborn screening (NBS), 1 in 294 newborns is identified with a condition leading to early treatment, and in some cases, life-saving interventions. Rapid advancements in genomic technologies to screen, diagnose, and treat newborns offers the promise of significantly expanding the number of diseases and individuals impacted by NBS. However, expansion of NBS occurs slowly in the United States (US) and almost always occurs condition by condition and state by state with the goal of screening for all conditions on a federally recommended uniform panel. The NBS Expansion Study sought to outline current practices, identify expansion challenges, and outline areas for improvement in NBS to enable the use of genomic discoveries. The Newborn Screening Translational Research Network (NBSTRN) designed this study to identify factors that impact NBS expansion and impede the use of genomics in the newborn period. The NBS Expansion Study included a workshop of experts, a survey of clinicians, and analysis of data from online repositories of state NBS programs, reports and publications of completed pilots, federal committee reports, and proceedings. The study confirmed that the capacity to expand NBS is variable across the US, and nationwide adoption of a new condition averages 9.5 years. This current approach is unsustainable and unresponsive to the rapid advances in screening and diagnostic technologies, the emergence of novel therapies, and the expectations of the public (or families/advocates).